Nest survival and predation in Blue-fronted Parrots Amazona aestiva: effects of nesting behaviour and cavity characteristics - Berkunsky, Igor (2016)
In this study we analyse factors affecting nest survival in Blue-fronted Parrots Amazona aestiva breeding in the Chaco region of northern Argentina. We combined temporal and environmental variables in order to determine which best explain variation in overall nest survival and in predation dependent nest survival. We predicted that high and deep cavities, that are inaccessible to snakes and other predators, would have high daily survival rates. We compared the relative effects on nest survival of time of the breeding season, stage of the nesting cycle, and characteristics of the nest cavity. We modelled daily survival rate (DSR) for all observed nests, and daily survival rate for nests that had been predated (daily survival rate in relation to predation exclusively, DSRp). Nest predation accounted for 50% of nest failures. DSR was on average 0.989, translating into an apparent hatching success of 0.39. DSR decreased with time of breeding and increased with nest age. DSRp decreased with time of breeding and inclination of the nest cavity entrance hole and increased with height from the ground of the entrance hole. There was a quadratic effect of nest age on DSRp, such that daily survival was highest during incubation, lowest at hatching and the early nestling stage, but increasing throughout the remainder of the nestling stage. This effect became more pronounced as the breeding season advanced. Year and observer effects did not affect the probability of survival. Temporal patterns and characteristics of the nest cavity explained most of the variation in nest survival in Blue-fronted Parrots, which highlights the relevance of including these covariates in future studies of nest survival in parrots, and has important management and conservation implications.